Knockdown of calponin 2 suppressed cell growth in gastric cancer cells - Jianwei Hu; Wenjuan Xie; Lingyue Shang; Xi Yang; Quanlin Li; Meidong Xu; Jianming Dou; Yiren Zhou; Weixin Niu; Yanhua Wu (Tumor Biology)
Calponin family members are actin filament–associated regulatory proteins with distinct expression patterns. Previous studies on CNN2 (calponin 2) have demonstrated that CNN2 is expressed in a broad range of tissues and cell types, exhibiting potential regulatory roles in a number of cellular activities, including cell proliferation, cell migration, and platelet adhesion. In this work, we found that both messenger RNA and protein expression levels of CNN2 were remarkably upregulated in 60%–70% of gastric cancer tissues by comparison with those of neighboring non-tumorous mucosa. By utilizing specific shCNN2 (small hairpin RNA targeting CNN2 ), the potential role of CNN2 in regulating AGS gastric cancer cell growth was then further investigated. AGS cells infected with shCNN2 exhibited significantly decreased cell growth ability by comparison with control cells in vitro. Moreover, while there was no obvious difference in cell cycle distribution between two groups, enhanced cell apoptosis was detected in cells with reduced CNN2 expression. Consistently, caspase 3/7 activity was also remarkably activated upon shCNN2 lentivirus infection. Taken together, our results demonstrated that knockdown of endogenous CNN2 in AGS cells could significantly activate cell apoptosis pathway and therefore suppress cell growth in vitro. The deletion of CNN2 might be a potential therapeutic approach to inhibit aggressive growth of gastric cancer.